Pengaruh Motivasi Kerja, Disiplin Kerja, dan Fasilitas Kantor Terhadap Kinerja Pegawai pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Medan - Sitorus, Nisa Br; Sembiring, Rasmulia; Panjaitan, Maludin (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to determine work motivation, work discipline, and office facilities in improving employee performance at the Medan City BKPSDM Office. The research method used in this research is quantitative descriptive research method. The sample in this study were all employees of the Medan Human Resources Staffing and Development Agency totalling 67 people because of the small sample size, the authors used the saturated sampling technique. Based on the results of the t hypothesis test, it is known that work motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, work facilities have a positive and significant effect on employee performance. Based on the results of the F hypothesis test, it is known that work motivation, work discipline, and work facilities simultaneously have a positive and significant effect on employee performance. Based on the results of the coefficient of determination analysis, it is known that the Adjusted R Square value is 0.790, which means that the employee performance variable can be explained by the work motivation, work discipline, and work facilities variables in this study by 79%, while the remaining 21% is other variables or factors.